Philosophical works of the late James Frederick Ferrier in three volumes - Ferrier, James Frederick (W. Blackwood and sons, 1875)
[v. 1] Institutes of metaphysic ... 3d ed., 1875.--v. 2. Lectures on Greek philosophy. New ed., 1888.--v. 3. [Philosophical remains] New ed., 1883.